Qualitative Exploration of Experiences and Consequences of Health-related Stigma among Indonesians with HIV, Leprosy, Schizophrenia and Diabetes - Rai, Sarju Sing; Irwanto, Irwanto; Peters, Ruth M.H.; Syurina, Elena V.; Putri, Annisa Ika; Mikhakhanova, Altana; Naniche, Denise; Zweekhorst, Marjolein B.M. (UI Scholars Hub, 2020)
Health-related stigma causes a negative impact on the lives of affected people and undermines the effectiveness of public health programs. This study aimedto explore experiences and consequences of stigma among people affected by four health conditions relevant in Indonesia– HIV (Human ImmunodeficiencyVirus), leprosy, schizophrenia and diabetes. In this qualitative study 40 people affected by the four health conditions in Jakarta and West Java, Indonesia–,were interviewed between March and June 2018. Data were analyzed thematically by following an integrative inductive-deductive approach. The experiencesand consequences of people with stigma were similar, but such experience were more severe among people affected by HIV, leprosy, and schizophrenia.Those with diabetes either experienced no or less severe stigma. The participants revealed that they experienced enacted stigma in healthcare, employment,and social interactions in the structural and interpersonal levels. They also experience the stigma in the form of internalized and anticipated stigma at an individual level. Incidences of human rights violations were evident. Social, behavioral, psychological, and medical consequences were also reported.